Analisis Pergeseran Fungsi pada Kesenian Gondang di Kampung Nagrog Desa Mandalagiri Kecamatan Leuwisari Kabupaten Tasikmalaya - Intan Ismawati Putri; Denden Setiaji; Wan Ridwan Husen (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research took the title “Analysis of Function Shift in Gondang Art in Kampung Nagrog, Desa Mandalagiri, Kecamatan Leuwisari, Kabupaten Tasikmalaya” aims to find out how the function shift in Gondang Art that occurred in Nagrog Village, Mandalagiri Village, Leuwisari District, Tasikmalaya Regency. This research focused on how the initial form of Gondang Art during its initial function and how the form of Gondang Art after experiencing a shift in function. This research uses descriptive qualitative research methods, data collection in this study was carried out by going to the field directly in the form of observation, interviews, and documentation which then became the source of data to be analyzed. The results of the findings made by researchers are the function shift that occurred in the Gondang Art in Nagrog Village which was influenced by the times.